Uma intervenção metodológica no ensino de computação em nuvem, utilizando contêineres Docker, Kubernetes e AWS de infraestrutura - Ciriaco, Maria Angelica da Costa (Departamento de Engenharias e Tecnologia - DETEC, 2025)
This work presents a methodological intervention that applies Cloud Computing concepts to the teaching of Docker and Kubernetes containers, utilizing the AWS platform as the infrastructure for developing a mini-course. To support the proposal, a Systematic Literature Review (SLR) was conducted, following the methodological procedures described by Kitchenham (2004), to identify teaching methodologies and assessment methods compatible with the course objectives. The SLR seeks to answer three main research questions: "RQ1: What are the methodologies applied in experience reports on the adoption of teaching/extension courses?", "RQ2: How are teaching/extension courses evaluated in the experience reports presented?", and "RQ3: What are the main outcomes sought in the experience reports on the implementation of teaching/extension courses?" The review results highlighted the effectiveness of active methodologies, such as the flipped classroom and problem-based learning, in the context of teaching technology through practice (RQ1). They also highlighted the interest in assessments that seek to capture the development of skills and competencies (RQ1). The main outcomes sought by the initiatives are related to the development of meaningful learning and critical thinking, areas that the courses aim to develop (RQ3).
Portugues
Keywords: CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO; Cloud computing; Docker; Kubernetes; AWS; Active learning; Computação em nuvem; Metodologias ativas